Efektivitas Pendekatan Teaching At The Right Level (TARL) terhadap Hasil Belajar Matematika Peserta Didik Kelas VI - Putri, Rochmah Anindia; Sulistyaningrum, Heny; Handayani, Sri; Hartono, Totok (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2025)
This study aims to evaluate the effectiveness of the Teaching at the Right Level (TaRL) approach in improving sixth-grade students' mathematics learning outcomes. The research was conducted using a Classroom Action Research (CAR) method over three cycles, which included the stages of planning, implementation, observation, and reflection. The subjects were 30 sixth-grade students at UPT SD Negeri Sidorejo 3 Tuban. Data were collected through achievement tests and student activity observation sheets. The findings indicate a significant improvement in student performance, as evidenced by the increase in average scores from 55.56 in the pre-cycle to 85.56 in the second cycle, with a mastery level reaching 96.67%. These results demonstrate that the TaRL approach is effective in addressing learning disparities among students in heterogeneous classrooms